In search of shrews of Chiapas: analysis of their distribution and conservation - Lorenzo, Consuelo; Bolaños-Citalán, Jorge; Navarrete-Gutiérrez, Darío; Pérez-López, José A.; Guevara, Lázaro (THERYA, 2019)
The state of Chiapas is home to multiple species of shrews (11 species), endemisms (three species from Mexico) and micro-endemisms (5 species from Chiapas). These species inhabit diverse physiographic regions and different types of habitats across the state. However, several are known by only very few specimens, mostly collected several years ago, making the knowledge about their natural history extremely scarce. This paper describes the efforts made by the authors along 16 years in search of shrews of Chiapas. Records were obtained from fieldwork, as well as by historical records from scientific collections and public databases. We estimated the relative abundances per species, identifying in each case the area of distribution and association with different types of vegetation and land use, current threats, and future research scenario for conservation purposes. The total trapping effort was 12,340 trap-nights across 13 sampling sites, with a total capture success of 0.18 %. In nine sampling sites, we succeeded in capturing 22 specimens of six species of shrews: Cryptotis griseoventris, C. lacandonensis, C. merriami, C. mexicanus, C. pueblensis, and Sorex cristobalensis. C. griseoventris had the highest relative abundance (31.81 %) and capture success (0.056), while C. lacandonensis showed the lowest relative abundance (4.54 %) and capture success (0.008). We present noteworthy records of shrews: 1) for being barely represented in scientific collections, as in C. griseoventris, and 2) for expanding the previously documented distribution area, as in C. lacandonensis and C. merriami. All of the species currently face serious conservation issues resulting from the loss of habitat. In particular, micro-endemic species such as S. sclateri and S. stizodon are seriously threatened. The specimens and records reported herein should foster further detailed research on the taxonomy, ecology, and biogeography to advance the knowledge of shrews inhabiting the southern border of Mexico.